2002
DOI: 10.1002/srin.200200207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al, Si and P on the kinetics of intercritical annealing of TRIP‐aided steels: thermodynamical prediction and experimental verification

Abstract: TRIP‐aided steels offer an excellent combination of strength and formability, which makes them particularly interesting for use in automotive applications. Recent investigations have shown that while the typical high CMnSi TRIP‐aided steel composition offers good mechanical properties, alloying with other elements or a modification of the processing are required to make this steel readily galvanizable without loss of the TRIP properties. Al‐alloying seems especially promising to realize this goal and P could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Some investigators [16][17][18] use the modified version of JMA model (Eq. (1)) to calculate volume fraction of austenite at different times.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators [16][17][18] use the modified version of JMA model (Eq. (1)) to calculate volume fraction of austenite at different times.…”
Section: )mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] It was shown that formation austenite in dual phase steels is a diffusion-controlled growth 8,9) and some of researchers proposed that [16][17][18] the empirical equation of Johnson-Mehl-Avrami (JMA) with Kolmogorov modification (JMAK) can be used for austenite transformation during intercritical annealing. The modified version of JMA model is as follows 19,20) : where f g is austenite volume fraction, t is annealing time, n is Avrami's exponent and k is the rate constant.…”
Section: Introductionmentioning
confidence: 99%
“…The presuppositions for the zinc wetting during the hot dip galvanization process are the existence of a reactive iron layer at the steel surface and a low concentration of non‐reducible oxides of alloying elements. Particularly high strength steels with high contents of Al, Si, or Mn tend to form such oxides which cannot be reduced at the temperatures applied in hot dip galvanization furnaces . The active iron layer at the steel sample is characterized by a high reflectivity.…”
Section: Measurement Conceptmentioning
confidence: 99%
“…For the study of the processes going on in continuous hot dip steel galvanization lines, Hot Dip Process Simulators (HDPS) are used . The composition of the gas phase near to the steel surface can be monitored by the introduction of a mass spectrometer probe into the HDPS .…”
Section: Introductionmentioning
confidence: 99%
“…During annealing of AHSS in continuous galvannealing as well as continuous galvanizing lines (CGL), formation of oxides of the alloying elements occurs. The process of selective oxidation, whether internal or external, is intensively discussed within recent research literature 3–7. Within this paper the interaction between the annealing atmosphere and the steel strip surface with each other will be referred to as heterogeneous gas/metal reactions.…”
Section: Introductionmentioning
confidence: 99%